Demographic Disparities in 30-Day Outcomes Following Achilles Tendon Repair - Dino Fanfan BSc; William Rittmeyer BS; Aditi Kumar BS; Daniel Murray MD; Cary B. Chapman MD (Foot & Ankle Orthopaedics)
Category: Sports; Ankle Introduction/Purpose: With more people participating in sporting activities, the occurrence of Achilles tendon rupture is increasing in the USA. Specific risk factors for Achilles tendon repair complications such as tobacco use, diabetes mellitus, steroid use, and obesity, have been well-reviewed in current literature. However, the impact of demographic disparities such as race and gender on the 30-day postoperative surgical complication of an Achilles tendon repair has not been extensively reported. Accordingly, we sought to investigate whether demographic disparities in 30-day postoperative Achilles repair outcomes exist and to what extent. Methods: The American College of Surgeons National Surgical Quality Improvement Program Database was queried for all patients undergoing surgical repair of Achilles tendon rupture from 2012 to 2021. Patients were identified using the common procedure terminology (CPT) codes 27650 and 27652. Patients were evaluated according to race and gender. A multivariate logistic regression was conducted for each complication to evaluate whether demographic factors independently were associated with complications after adjusting for various variables (age, obesity rate, diabetic/nondiabetic, smoker/nonsmoker, ASA class). Medical complications included rates of deep vein thrombosis (DVT), superficial surgical site infection (SSI), deep SSI (dSSI), wound disruption after surgery/dehiscence, readmission rate and reoperation rate. Results: A total of 6333 patients who underwent Achilles tendon were included in the study, 25% (N =1607) were women, 49.0% (N =3101) reported as White, 21.1% (N =1336) as Black/African American and 29.9% (N =1896) as Other. In our unadjusted analysis, there was a higher prevalence of DVT in white patients. Following a multivariate analysis, neither race or gender of the patient were associated with a difference in rates of all complications, wound, dSSI, wound disruption after surgery, readmission rate and reoperation rate. Only race demonstrated a significant difference in the rate of superficial SSI (χ2 = 7.21; p=.0272) following multivariate analysis. Conclusion: When adjusted for age, smoking, diabetes, obesity and ASA class, there was a statistically significant although clinically insignificant difference in superficial surgical site infection rate between white patients, black patients, and patients of other races not seen in any other post-operative outcome. In our unadjusted analysis, there was a higher prevalence of DVT in white patients possibly because these patients were generally older and DVTs are more common in elderly patients. This study highlights advancements in the delivery of equitable care, but we recognize that there continues to be disparities in surgical care which requires strong and worthwhile solutions.